Evaluation of the Rio de Janeiro State Flood Warning System: A Case Study for the Hydrographic Region of the Médio Paraíba do Sul (RJ), Brazil - de Pontes, Lídia Luisa Mota; França, José Ricardo de Almeida; de Carvalho, Lino Augusto Sander (Anuário do Instituto de Geociências, 2023)
This work is a case study for the Hydrographic Region of the Médio Paraíba do Sul located in the State of Rio de Janeiro (Brazil), which has natural disasters, such as floods, as the most recurrent. Due to the social, economic and environmental impacts that these disasters cause, this research aim to analyze the history of alerts issued by the Flood Warning System (FWS) and to assess its efficiency. Through the retro-analysis of Alert Trigger Events (ATE) that occurred in the monitored rivers, investigations were also carried out in the hydrological and meteorological scope. The results identified that the Attention stage belonging to the operational protocol significantly reduces the efficiency of the FWS about sending alerts, causing high false alarm rate. Regarding the influence that variation in the type of data transmission has on the Operational Protocol in RH-III, it is considered that the time interval between data transmission and their availability on the State Environmental Institute (SEI) erver generates a false alarm, however the FWS is still efficient. Barra Mansa River is the only one that has flood events, which raises questions about the representativeness of the other stations spread across RH-III. In addition, 60% of alerts issued for RH-III were related to episodes of Cold Fronts and South Atlantic Convergence Zones. These information helps improve the description of the flood events in the region. Rainfall Anomaly Index (RAI) identified periods that the rainfall rate was below the climatological average, indicating a drier environment, but with alerts issued.